1991
DOI: 10.1083/jcb.112.3.441
|View full text |Cite
|
Sign up to set email alerts
|

Two types of Chlamydomonas flagellar mutants missing different components of inner-arm dynein.

Abstract: Abstract. Two types of Chlamydomonas reinhardtii tlagellar mutants (idaA and idaB) lacking partial components of the inner-arm dynein were isolated by screening mutations that produce paralyzed phenotypes when present in a mutant missing outer-arm dynein. Of the currently identified three inner-arm subspecies I1, 12, and 13, each containing two heterologous heavy chains (Piperno, G., Z. Ramanis, E. E Smith, and W. S. Sale. 1990. J. Cell Biol. 110:379-389), idaA and idaB lacked I1 and 12, respectively. The 13 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
175
1
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(195 citation statements)
references
References 34 publications
15
175
1
1
Order By: Relevance
“…In this study, the principal components summarize the major patterns of variation among axonemes isolated from multiple strains and induced to slide in Table 1. Chlamydomonas strains used in this study Strain Structural/motility defect A54-e18 no axonemal structural defect/wild-type motility (Smith and Lefebvre, 1996) 137c no axonemal structural defect/wild-type motility (Harris, 1989) oda1, pf28 lack outer dynein arms/flagella beat with one-half frequency (Kamiya and Okamoto, 1985;Mitchell and Rosenbaum, 1985) ida1, pf30 lacks inner dynein arm subform I1/ reduced beat frequency, altered waveform (Brokaw and Kamiya, 1987) pf30pf28 lacks outer dynein arms and inner dynein arm I1 (Piperno et al, 1990;Smith and Sale, 1992) pf3 defects in dynein regulatory complex/reduced beat frequency, altered waveform (Brokaw and Kamiya, 1987;Kamiya et al, 1991;Piperno et al, 1992) pf6 central apparatus, lacks 1A projection/flagella paralyzed or twitch (Dutcher et al, 1984) cpc1 central apparatus, lacks 1B projection/reduced beat frequency (Mitchell and Sale, 1999) pf14 lacks radial spokes/paralyzed flagella (Piperno et al, 1977) pf17 lacks radial spoke heads/paralyzed flagella (Huang et al, 1981) Fig conditions of low and high Ca 2+ buffer; these analyses revealed major trends in microtubule sliding patterns and the identities of doublet microtubules with active dynein arms. The results of the PCs analyses for each variable set are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the principal components summarize the major patterns of variation among axonemes isolated from multiple strains and induced to slide in Table 1. Chlamydomonas strains used in this study Strain Structural/motility defect A54-e18 no axonemal structural defect/wild-type motility (Smith and Lefebvre, 1996) 137c no axonemal structural defect/wild-type motility (Harris, 1989) oda1, pf28 lack outer dynein arms/flagella beat with one-half frequency (Kamiya and Okamoto, 1985;Mitchell and Rosenbaum, 1985) ida1, pf30 lacks inner dynein arm subform I1/ reduced beat frequency, altered waveform (Brokaw and Kamiya, 1987) pf30pf28 lacks outer dynein arms and inner dynein arm I1 (Piperno et al, 1990;Smith and Sale, 1992) pf3 defects in dynein regulatory complex/reduced beat frequency, altered waveform (Brokaw and Kamiya, 1987;Kamiya et al, 1991;Piperno et al, 1992) pf6 central apparatus, lacks 1A projection/flagella paralyzed or twitch (Dutcher et al, 1984) cpc1 central apparatus, lacks 1B projection/reduced beat frequency (Mitchell and Sale, 1999) pf14 lacks radial spokes/paralyzed flagella (Piperno et al, 1977) pf17 lacks radial spoke heads/paralyzed flagella (Huang et al, 1981) Fig conditions of low and high Ca 2+ buffer; these analyses revealed major trends in microtubule sliding patterns and the identities of doublet microtubules with active dynein arms. The results of the PCs analyses for each variable set are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Axonemes isolated from both pf3 and ida1 (pf30) display altered waveforms when reactivated in vitro; in low Ca 2+ buffer these mutant axonemes beat at reduced frequency with a smaller shear amplitude compared to wildtype axonemes (Brokaw and Kamiya, 1987;Kamiya et al, 1991). This reduction in shear amplitude reduces the asymmetry (increases the symmetry) of the propagating wave.…”
Section: Sliding Pattern Correlates With Waveformmentioning
confidence: 99%
“…Three strains, oda/, ida/and ida4, missing the outer arms, the n inner arms and the I2 inner arms, respectively (16,18), retain the 75-kD proteins (Fig. 8, C-E).…”
Section: Localization Of the 75-kd Proteins Vclthin The Axonemementioning
confidence: 99%
“…Indeed, strains that lack various subsets of inner arms exhibit defects in waveform associated with reductions in shear amplitude (4). Subspecies f, or inner arm I1, contains 2 HCs 1 (1␣ and 1␤), three ICs (IC110, IC138, and IC140), and several LCs, including LC8 and Tctex1 (7)(8)(9)(10)(11)(12)(13). Both the 1␣ and 1␤ HCs are essential for the assembly of inner arm I1 (9,14), and a truncated 1␤ HC fragment containing the N-terminal ϳ113 kDa but lacking the motor domain is sufficient for this activity (14).…”
mentioning
confidence: 99%